Selected Aspects of Knowledge Management in the Care of Dementia Patients - Skibiński, Andrzej; Klufová, Renata; Kozlová, Lucie (European Journal of Sustainable Development, 2025)
Dementia is characterized by a progressive cognitive decline, memory impairment, and disability. Alzheimer’s disease (AD) accounts for 60–70% of cases, followed by vascular and mixed dementia. Given the projected trends in population ageing and population growth, the number of people with dementia is expected to increase. Stakeholders involved in community dementia support services often work on their own and without coordination with other services. These circumstances can result in a lack of information and support for people with dementia and their family caregivers at home. Caregivers of people with dementia find it extremely difficult to choose the best care method because of complex environments and the variable symptoms of dementia. This contribution aims to assess and compare community health professionals’ dementia knowledge, attitudes and care approaches in Poland and the Czech Republic Keywords: knowledge management, dementia care, healthcare